Mary Daly's (1928-2010) theological method of ontolinguistic hermeneutics - Wozna, Antonina Maria (Springer, 2024)
"Ontolinguistics theological Hermeneutics: sources and Daly's proposal analyses the method used by Mary Daly, her constructive criticism of the traditional theological method and her proposal to combine the best insights of the Christian tradition, hermeneutic philosophy and feminist theology. The book brings together the inputs of a pioneer in feminist theology Mary Daly on the much-debated issue of theology as method. This book, along with Antonina Wozna's Theological hermeneutics and Daly's verification process are important reads for scholars working in the intersection of theology, gender and feminism"--